Construcción de ciudadanía a través del periodismo de opinión de Diario Los Andes, enero - junio 2022 - Villacis Chiluisa, Jhonathan Sanatiago (2024)
ABSTRACT: This study investigates the contribution of opinion journalism from Diario Los Andes in the construction of citizenship in Ecuador, specifically during the first semester of 2022. With the aim of exploring and identifying how this medium influences the civic formation process, it is carried out an in-depth analysis of the content published between January and June 2022, covering a diversity of journalistic genres, including opinion articles, editorials, cartoons and famous phrases. The study initially focused on establishing the content published by Diario Los Andes during the aforementioned period. A wide range of themes were identified that reflect a concern for political, social, economic and cultural issues. This thematic diversity provided a solid basis for the analysis of the role of journalism in the formation of a wellinformed and engaged citizenry. Subsequently, the specific contribution of these journalistic genres in the construction of citizenship was analyzed. The results indicated that the opinion journalism of Diario Los Andes plays a vital role in promoting public debate, critical reflection and active participation in matters of national interest.